Broken business seven steps to reform good companies gone bad - Hernandez, José R. 1974- (Gildan, 2019)
Broken Business: Seven Steps to Reform Good Companies Gone Bad is an essential book for leaders seeking a concise review at how things can go wrong, how to deal with scandal fallout, and how to ultimately become a better company.
Online resource; title from title details screen (OverDrive, viewed April 5, 2019)
Keywords: Corporate governance; Corporations -- Corrupt practices -- Prevention; Gouvernement d'entreprise; BUSINESS & ECONOMICS; Conflict Resolution & Mediation; Corporations; Corrupt practices; Prevention; Downloadable audio books; Audiobooks; Livres audio